Differential Stability of Flamingo Protein Complexes Underlies the Establishment of Planar Polarity - Strutt, Helen (Cell Press, 2008)
BACKGROUND: The planar polarization of developing tissues is controlled by a conserved set of core planar polarity proteins. In the Drosophila pupal wing, these proteins adopt distinct proximal and distal localizations in apicolateral junctions that act as subcellular polarity cues to control morphological events. The core polarity protein Flamingo (Fmi) localizes to both proximal and distal cell boundaries and is known to have asymmetric activity, but the molecular basis of this asymmetric activity is unknown. RESULTS: We examine the role of Fmi in controlling asymmetric localization of polarity proteins in pupal wing cells. We find that Fmi interacts preferentially with distal-complex components, rather than with proximal components, and present evidence that there are different domain requirements for Fmi to associate with distal and proximal components. We further show that distally and proximally localized proteins cooperate to allow stable accumulation of Fmi at apicolateral junctions and present evidence that the rates of endocytic trafficking of Fmi are increased when Fmi is not in a stable asymmetric complex. Finally, we provide evidence that Fmi is trafficked from junctions via both Dishevelled-dependent and Dishevelled-independent mechanisms. CONCLUSIONS: We present a model in which the primary function of Fmi is to participate in the formation of inherently stable asymmetric junctional complexes: Removal from junctions of Fmi that is not in stable complexes, combined with directional trafficking of Frizzled and Fmi to the distal cell edge, drives the establishment of cellular asymmetry.